Shaping Relationships with Nature – Adaptation to Climate Change as a Challenge for Society - Görg, Christoph (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
Climate change has become a highly politicised issue over the last couple of years. In particular adaptation to climate change raises fundamental conceptual challenges concerning the interplay of societal and biophysical processes. The paper discusses some of these challenges and introduces a theoretical concept able to improve our understanding of the complex interactions between nature and society. The concept of ‘societal relationships with nature’, which originated in the so-called ‘Frankfurt School’ of critical theory, provides a dialectic approach towards these complex interactions able to deal with the societal causes of climate change as much as with the repercussions of global warming on societies, including the claim for balancing mitigation and adaptation needs. Basically, the goal of sustainable development has returned on the agenda in a new form: To what extent are societies in the ‘North’ and ‘South’ respectively able to deal with the vulnerabilities created or heightened by climate change? In this context, the spatial dimension of climate policy at and between the different spatial scales is becoming an ever more pressing problem, which is illustrated using the transformation of ecosystem services as a case study.